SOME RESULTS ON STRONGLY π-REGULAR RIN - Sinan O. Al-Salihi; Emad I. Jassim (Tikrit Journal of Pure Science)
In this paper we study the strongly - regular ring (for short   st. -reg. rg.) and some properties also give some new results of st.  -reg. rg. and its connection with other rings.